Analysis of Base and Non-base Sectors and Economic Conpetitiveness in Magetan Regency - Salsabila Nuri Winanda; Riko Setya Wijaya; Putra Perdana (Finance : International Journal of Management Finance, 2026)
This study aims to analyze the economic potential and competitiveness of Magetan Regency using the Location Quotient (LQ), Shift Share, and Klassen Typology methods based on 2019–2023 BPS data. The results indicate eight basic sectors, ten sectors driving economic growth, nine sectors with relatively rapid growth, twelve highly competitive sectors, and five sectors included in Quadrant I, designated as advanced and fast-growing sectors.